코로나19 전담병동 간호사의 죽음태도, 자아존중감과 호흡기 감염병 위험인식이 죽음불안에 미치는 영향 - 정연희; Jeong Yeon Hee; 조헌하; Cho Hun Ha (정신간호학회지, 2025)
Purpose: To provide foundational data for developing death anxiety intervention programs for nurses by identifying the factors influencing their death anxiety in COVID-19 wards. Methods: This descriptive survey study involved 123 nurses who had worked for more than six months in the COVID-19 wards of a tertiary hospital in Metropolitan B City. Data were collected using a structured self-report questionnaire from March 22 to April 9, 2022. Results: Death anxiety differed significantly by gender (t=-3.32, p=.001). It showed a significant positive correlation with the perceived risk of respiratory infectious disease (r=.29, p=.001) but significant negative correlations with death attitude (r=-.69, p<.001) and self-esteem (r=-.18, p=.049). Factors influencing death anxiety included death attitude (β=-.67, p<.001) and gender (β=.23, p<.001), accounting for 52.4% of the variance. Conclusion: This study found that death attitude and gender significantly influenced death anxiety among nurses in COVID-19 wards. Therefore, it is neccessary to develop and apply gender-sensitive death anxiety intervention programs that could positively and effectively influence death attitudes to reduce death anxiety of nurses in covid-19 wards.